Coming of Age: Gurung Women (Mustang, Nepal) and Ute Women (Colorado, USA) - Rauniyar, Binay Kumar (Literary Studies, 2022)
Gurung women of Mustang, Nepal, and Ute women of Colorado, USA, are fascinating people and subjects. They have upheld matriarchy in the predominantly patriarchal world. Their free, symphonic life presents a model for other women. The two tribal womenfolk living in two different poles show keen relations regarding many customs and rituals as well as in displaying women power. It is an interesting and meaningful study to compare the societies of these two tribal womenfolk and trace their relationship with one another. They may have been distantly related to each other in their origin as such studies imply about them.